2023
DOI: 10.3390/ph16050670
|View full text |Cite
|
Sign up to set email alerts
|

Nanogel Containing Gamma-Oryzanol-Loaded Nanostructured Lipid Carriers and TiO2/MBBT: A Synergistic Nanotechnological Approach of Potent Natural Antioxidants and Nanosized UV Filters for Skin Protection

Abstract: The human skin is a recurring target of external aggressions, such as UV radiation, leading to exacerbation of the aging process and the occurrence of skin diseases, such as cancer. Hence, preventive measures should be taken to protect it against these aggressions, consequently decreasing the chance of disease development. In the present study, a topical xanthan gum nanogel containing gamma-oryzanol-loaded nanostructured lipid carriers (NLCs) and nanosized UV filters TiO2 and methylene bis-benzotriazolyl tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Dendrimers made of dendritic polyglycerol (dPG) were employed to create hydrophilic and thermo-responsive three-dimensional cross-linked nanogels that let small and big molecules penetrate SC and concentrate in hair follicles [221]. Badalkhani et al [222] formulated γ-oryzanol-loaded NLCs and nanosized UV filters TiO 2 to evaluate the synergistic potential for skin protection against diseases such as cancer. Studies have shown that nanogel loaded with NLCs and nano UV filters had excellent long-term storage stability and photoprotection capabilities, which might be useful for protection against UV-generated skin cancer.…”
Section: Nanogelsmentioning
confidence: 99%
“…Dendrimers made of dendritic polyglycerol (dPG) were employed to create hydrophilic and thermo-responsive three-dimensional cross-linked nanogels that let small and big molecules penetrate SC and concentrate in hair follicles [221]. Badalkhani et al [222] formulated γ-oryzanol-loaded NLCs and nanosized UV filters TiO 2 to evaluate the synergistic potential for skin protection against diseases such as cancer. Studies have shown that nanogel loaded with NLCs and nano UV filters had excellent long-term storage stability and photoprotection capabilities, which might be useful for protection against UV-generated skin cancer.…”
Section: Nanogelsmentioning
confidence: 99%
“…The findings revealed even further promise for the usability of GO as a means of transportation for effective delivery to reduce skin irritation and skin neoplasia and improve skin-aging protection and wrinkle improvement. The semi-purified rice bran extracts (GO being one of them) formulated into topical creams and gels not only stimulated the proliferation of human fibroblasts and inhibited MMP-2 activity, but they also improved skin attributes such as hydration, pigmentation, thickness, and roughness, and skin elasticity [119,122]. These results enhance the understanding of topical dermatological products that can be used to reduce photoaging and skin texture; however, further studies would benefit an adequate vehicle and form, such as gels and creams.…”
Section: Gamma Oryzanolmentioning
confidence: 99%